Determinants of Banks Private Sector Credit Supply in Tanzania - Mwankemwa, Suma (African Journal of Accounting and Social Sciences, 2024)
What determines the supply of private sector credit is an issue of policy and research interest in Tanzania. Using the Autoregressive Distributed Lag (ARDL) framework, this paper examines relevant factors influencing the supply of private sector credit by banks after the liberalization of the financial sector in Tanzania. The results revealed that a model with real private sector credit as the dependent variable was superior to the alternative model, and real short term lending rate was statistically a superior regressor compared to the real overnight bank lending rate. Moreover, it was found that bank deposits is an unimportant determinant of private sector credit, and that growth and inflation respectively had positive and negative effects on bank credit supply. The results also suggested that real bank credit growth was co-integrated with its determinants over the long run. The results from the analysis imply that policy should focus on policy interventions which promote economic growth, healthy bank balance sheets, and reasonable spread as motivating factors for banks to enhance supply of private sector credit in the country.